Federal Rules of Criminal Procedure (Open textbook library., 2014)
This series of Federal Rules books, consisting of the Federal Rules of Evidence, Criminal Procedure and Civil Procedure, are powered by the Legal Information Institute at Cornell Law School, and created in partnership with The Center for Computer-Assisted Legal Instruction (CALI).These rules govern the conduct of all criminal proceedings brought in Federal courts. Our Federal Rules ebooks include: The complete rules as of December 1, 2012 (for the 2013 edition). All notes of the Advisory Committee following each rule. Internal links to rules referenced within the rules. External links to the LII website's version of the US Code.